Integration of Genetic and Reproductive Counseling with Psychotherapy: Considerations Through a Case - Monros, Eugenia; Junyent, Assumpta (Revista de Psicoterapia, 2017)
The main objective of this article is to invite clinical psychologists and psychotherapists to penetrate the world of rare genetic diseases and think over the emotional and psychosocial impact they have on the individual. Beyond the informative act of genetic counseling, both those affected and their families often need a deep psychotherapeutic process to overcome the traumatic aspects and grief which are often associated with the disease. From an integrative look, the process should also include the bio-psycho-social support to promote access to health and associative resources. In short, the patient and/or the family need to be helped to rebuild and re-tell their life in a more autonomous and healthy way. A clinical case is presented to illustrate the need to include psychotherapy into genetic counseling.